A quantitative transcriptome reference map of the normal human hippocampus. Issue 1 (14th July 2015) - Caracausi, Maria; Rigon, Vania; Piovesan, Allison; Strippoli, Pierluigi; Vitale, Lorenza; Pelleri, Maria Chiara
ABSTRACT: We performed an innovative systematic meta‐analysis of 41 gene expression profiles of normal human hippocampus to provide a quantitative transcriptome reference map of it, i.e. a reference typical value of expression for each of the 30, 739 known mapped and the 16, 258 uncharacterized (unmapped) transcripts. For this aim, we used the software called TRAM (Transcriptome Mapper), which is able to generate transcriptome maps based on gene expression data from multiple sources. We also analyzed differential expression by comparing the hippocampus with the whole brain transcriptome map to identify a typical expression pattern of this subregion compared with the whole organ. Finally, due to the fact that the hippocampus is one of the main brain region to be severely affected in trisomy 21 (the best known genetic cause of intellectual disability), a particular attention was paid to the expression of chromosome 21 (chr21) genes. Data were downloaded from microarray databases, processed, and analyzed using TRAM software. Among the main findings, the most over‐expressed loci in the hippocampus are the expressed sequence tag cluster Hs.732685 and the member of the calmodulin gene family CALM2 . The tubulin folding cofactor B ( TBCB ) gene is the best gene at behaving like a housekeeping gene. The hippocampus vs. the whole brain differential transcriptome map shows the over‐expression of LINC00114, a long non‐coding RNA mapped on chr21. The hippocampus transcriptome map was validated in vitro by assaying gene expression through several magnitude orders by "Real‐Time" reverse transcription polymerase chain reaction (RT‐PCR). The highly significant agreement between in silico and experimental data suggested that our transcriptome map may be a useful quantitative reference benchmark for gene expression studies related to human hippocampus. Furthermore, our analysis yielded biological insights about those genes that have an intrinsic over‐/under‐expression in the hippocampus. © 2015 Wiley Periodicals, Inc.